Mood and perceived social support of Colombian older adults with chronic obstructive pulmonary disease during the pandemic: A cross-sectional descriptive study - Restrepo, Jorge Emiro; Ospina-Bran, Zaira Eliana; Cuartas-Montoya, Gina Paula (Gaceta Médica de Caracas, 2022)
Background: During the pandemic, older adults have been one of the most vulnerable groups. Having a clinical diagnosis of COPD significantly increases the likelihood of poor clinical outcomes in patients with COVID-19, so these patients should be considered a high-risk group. From a positive mental health perspective, it is important to know patients’ moods and perceived social support.